2000
DOI: 10.1021/jm0001727
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Function Studies on the New Growth Hormone-Releasing Peptide, Ghrelin:  Minimal Sequence of Ghrelin Necessary for Activation of Growth Hormone Secretagogue Receptor 1a

Abstract: The recently discovered growth hormone secretagogue, ghrelin, is a potent agonist at the human growth hormone secretagogue receptor 1a (hGHSR1a). To elucidate structural features of this peptide necessary for efficient binding to and activation of the receptor, several analogues of ghrelin with various aliphatic or aromatic groups in the side chain of residue 3, and several short peptides derived from ghrelin, were prepared and tested in a binding assay and in an assay measuring intracellular calcium elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
424
3
23

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 518 publications
(475 citation statements)
references
References 18 publications
21
424
3
23
Order By: Relevance
“…The same action was found to be exerted by des-Gln 14 -ghrelin, another natural acylated form of ghrelin derived from an alternative splicing of the ghrelin gene also capable of binding the GHS type 1a receptor (Hosoda et al, 2000a). However, we have now found unexpectedly that non-acylated ghrelin was able to exert the same action at even greater extent than the acylated forms of ghrelin, even though unacylated ghrelin is generally assumed to be devoid of biological activity (Kojima et al, 2001), as it cannot bind and activate the GHS type 1a receptor (Bednarek et al, 2001). Although GHS type 1a receptor expression at the myocardial level has been demonstrated (Nagaya and Kangawa, 2003), the existence of GHS receptor subtypes in the heart has been already shown .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The same action was found to be exerted by des-Gln 14 -ghrelin, another natural acylated form of ghrelin derived from an alternative splicing of the ghrelin gene also capable of binding the GHS type 1a receptor (Hosoda et al, 2000a). However, we have now found unexpectedly that non-acylated ghrelin was able to exert the same action at even greater extent than the acylated forms of ghrelin, even though unacylated ghrelin is generally assumed to be devoid of biological activity (Kojima et al, 2001), as it cannot bind and activate the GHS type 1a receptor (Bednarek et al, 2001). Although GHS type 1a receptor expression at the myocardial level has been demonstrated (Nagaya and Kangawa, 2003), the existence of GHS receptor subtypes in the heart has been already shown .…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the most significant influence on contractility of the papillary muscle was exerted by des-octanoyl ghrelin, an unacylated form devoid of any endocrine action (Kojima et al, 2001;Torsello et al, 2002) because this form, unlike octanoylated ghrelin and des-Gln 14 -ghrelin (Hosoda et al, 2000a), is unable to bind the classical GHS type 1a receptor (Bednarek et al, 2001). The binding studies performed here with either acylated and unacylated ghrelin demonstrated that there is a specific receptor recognized by all ghrelin forms and by hexarelin as well; these findings therefore indicate the existence of a cardiac non-GHS type 1a receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that C-terminal elongation of ghrelin hardly induces differences in potency [36], it is unknown whether this has an effect on desensitization. Using HEK293 cells stably transfected with the hGHSR, we also investigated different truncated forms of ghrelin.…”
Section: Ghsr Desensitization Is Essential For the Anticonvulsant Effmentioning
confidence: 99%
“…It is the natural ligand of the GHSR-1a receptor [1]. For it to act on the GHSR-1a ghrelin has an n-octanoic acid modification on serine 3 residue [2].The ghrelin gene is located in chromosome 3 (3p25-26) [1], contains four preproghrelin-coding exons, and encodes a precursor of 117aa (preproghrelin) with 82% of homology between species [3]. As a result of alternative splicing of this gene, a 27 aa acylated peptide was identified with the same activity potency as ghrelin (des-Gln14-ghrelin) [4].…”
mentioning
confidence: 99%